Aktualisasi Program 7 Kebiasaan Anak Indonesia Hebat Era Digitalisasi Di SMAS NU Toboali - Fauzi; Siti Patimah; Nur Hidayah; M. Indra Saputra (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study aims to analyze the implementation and relevance of the